Tailoring STrAtegies for RelaTives for Black and South Asian dementia family carers in the United Kingdom: A mixed methods study. (15th January 2023) - Webster, Lucy; Amador, Sarah; Rapaport, Penny; Mukadam, Naaheed; Sommerlad, Andrew; James, Tiffeny; Javed, Sabrina; Roche, Moïse; Lord, Kathryn; Bharadia, Trishna; Rahman‐Amin, Malayka; Lang, Iain; et al.
Abstract: Objectives: We culturally adapted STrAtegies for RelaTives (START), a clinically and cost‐effective intervention for dementia family carers, for Black and South Asian families. It had previously been delivered to family carers around the time of diagnosis, when most people with dementia had very mild, mild or moderate dementia. Methods: We interviewed a maximum variation sample of family carers (phase one; n  = 15 South Asian; n  = 11 Black) about what aspect of START, required cultural adaptation, then analysed it thematically using the Cultural Treatment Adaptation Framework then adapted it in English and into Urdu. Facilitators then delivered START individually to carers (phase two; n  = 13 South Asian; n  = 8 Black). We assessed acceptability and feasibility through the number of sessions attended, score for fidelity to the intervention and interviewing family carers about their experiences. We used the Hospital Anxiety and Depression Scale. to examine whether immediate changes in family carers' mental health were in line with previous studies. Results: In phase one we made adaptations to peripheral elements of START, clarifying language, increasing illustrative vignettes numbers, emphasising privacy and the facilitator's cultural competence and making images ethnically diverse. In phase two 21 family carers consented to receive the adapted intervention; 12 completed ≥5/8 sessions; four completed fewer sessions and five never started. Baseline HADS score ( n  = 21) was 14.4 (SD = 9.8) but for those who we were able to follow up was 12.3 (SD 8.1) and immediately post‐intervention was 11.3 ( n  = 10; SD = 6.1). Family carers were positive about the adapted START and continued to use elements after the intervention. Conclusions: Culturally adapted START was acceptable and feasible in South Asian and Black UK‐based family carers and changes in mental health were in line with those in the original clinical trial. Our study shows that culturally inclusive START was also acceptable. Changes made in adaptations were relevant to all populations. We now use the adapted version for all family carers irrespective of ethnicity. Key points: Making interventions culturally tailored is important for dementia family carers from ethnic minorities. The culturally adapted STrAtegies for RelaTives (START) intervention was acceptable and feasible in South Asian and Black dementia family carers. There were also similar improvements in mental health in comparison to those in the trial of the original START intervention.